Association between asthma and falls: A nationwide population-based study. (3rd July 2018) - Chung, Jae Ho; Kim, Tae Ho; Han, Chang Hoon
ABSTRACT: Objectives : We evaluated the relationship between asthma and falls in Koreans using data from a large population-based cross-sectional survey. Methods : Data were obtained from 228, 642 participants, of whom 6, 372 had asthma, who participated in the 2013 Korean Community Health Survey. We explored the risk of falls after adjusting for sociodemographic factors and comorbidities. Logistic regression was used to identify risk factors for falls in asthmatics. Patients with asthma who had been diagnosed by a physician were included after excluding those who did not respond to the self-reported questionnaire. Results : In all, 1, 733/6, 372 (27.1%) asthma patients and 258/788 (32.7%) patients with uncontrolled asthma (who had visited the emergency room because of asthma exacerbation in the prior 12 months) reported histories of falls. In asthmatics, the crude odds ratio (OR) for falls was 1.57 (95% confidence interval [CI]: 1.48–1.67); the OR for falls in the group with uncontrolled asthma was 2.13 (95% CI: 1.83–2.47). The multivariate OR for falls in the asthma group (compared to the non-asthma group) was 1.27 (95% CI, 1.18–1.35) and the OR for falls in the uncontrolled asthma group (again compared to the non-asthma group) was 1.55 (95% CI, 1.32–1.82). Subgroup analysis of the adjusted ORs for falls in asthmatics by age group revealed a significant difference between the presence of asthma and uncontrolled asthma, and falls, in each age group, similar to the relationship evident in the total adult population. Conclusion : Asthma is associated with falls, even after adjusting for sociodemographic and comorbid variables.